" تحليل البيئة الداخلية كمدخل استراتيجي لتحسين جودة الخدمات التعليمية " دراسة ميدانية بالمعهد العالي للعلوم والتقنية صبراتة (Comprehensive Journal of Science, 2026)
This study addressed the topic of "Analyzing the Internal Environment as a Strategic Approach to Improving the Quality of Educational Services." It was an empirical study conducted at the Higher Institute of Science and Technology in Sabratha.The primary aim of the study was to diagnose the strengths and weaknesses within the institute and to assess how each affects the quality of educational services provided. The main research question addressed was:Can the analysis of the internal environment be relied upon to improve the quality of educational services at the Higher Institute of Science and Technology in Sabratha?The study employed a descriptive analytical approach through field research. The population consisted of faculty members and administrative leaders at the institute. A questionnaire was utilized as the main tool for data collection from a purposive sample of 38 respondents.The analysis focused on three key areas: demographic characteristics, diagnosing strengths and their significance, and identifying weaknesses and their degree of impact.The study's key findings revealed several competitive advantages (strengths) that the institute possesses, chief among them its strategic geographic location that allows for investment and the creation of self-financing sources. The results also indicated that the institute has a good academic reputation and offers specializations that meet labor market needs, along with a culture of mutual respect among the staff.Conversely, the analysis uncovered structural challenges (weaknesses) that adversely affect performance, most notably the weakness of the approved annual budget and a near-total reliance on government funding.The results also highlighted a shortage of teaching staff in some specializations, as well as a lack of modern equipment in laboratories and workshops, alongside insufficient skills among staff in handling electronic management systems and total quality management.The study recommended the need to leverage the institute's geographic location to diversify income sources and to develop a clear strategy that ensures adherence to job descriptions. It also emphasized the importance of intensifying training programs for staff to transition towards digital management and providing the necessary financial support to enhance laboratories and workshops, ensuring educational outputs align with global quality standards.